The Acid–Base Balance and Gender in Inflammation: A Mini-Review - Casimir, Georges Jacques; Lefèvre, Nicolas; Corazza, Francis; Duchateau, Jean; Chamekh, Mustapha (Frontiers in Immunology, 2018)
In humans, acid-base balance is crucial to cell homeostasis. Acidosis is observed in numerous inflammatory processes, primarily acute conditions like sepsis, trauma, or acute respiratory distress where females tend to exhibit better prognosis compared with males. The mechanisms underlying these gender-dependent differences are multiple, probably involving hormonal and genetic factors, particularly the X chromosome. Although pH influences multiple immunological functions, gender differences in acid-base balance have been poorly investigated. In this review, we provide an update on gender differences in human susceptibility to inflammatory diseases. We additionally discuss the potential impact of acid-base balance on the gender-bias of the inflammatory response in view of our recent observation that girls present higher neutrophilic inflammation and lower pH with a trend towards better prognosis in severe sepsis. We also highlight the potent role played by endothelial cells in gender differences of inflammation through activation of proton-sensing G protein-coupled receptors.